ASPEK KESELAMATAN PADA APLIKASI REAKTOR NUKLIR SUHU TINGGI UNTUK PROSES STEAM REFORMING GAS ALAM - Djati Hoesen Salim (Jurnal Pengembangan Energi Nuklir, 2008)
ABSTRACTSAFETY ASPECT OF HIGH TEMPERATURE NUCLEAR REACTOR APPLICATION FOR NATURAL GAS STEAM REFORMING. An assessment of the safety aspect of high temperature nuclear reactor application for natural gas steam reforming has been carried out. The basic safety aspect associated with nuclear coupling to chemical process is to prevent the release of radioactive materials to the environment and or the chemical process. In utilizing nuclear heat for chemical process, intermediate heat exchanger (IHX) is used as an interface that separates nuclear and non nuclear zones. IHX is helium-helium heat exchanger in which the primary helium (905oC) coming out from the reactor, and transfer its heat to the secondary helium gas (890oC). To prevent possible release of radioactive materials from nuclear zone, balanced pressure is applied. The pressure of chemical process (4.5 MPa) is designed to be higher than the pressure of secondary helium (4.1 MPa) or primary helium (4 MPa). The design of balance pressure and the use of IHX cause some inferior condition of the nuclear heated reformer since the lower temperature (~800oC) reaches catalyst tube of reformer. This condition gives impact on lower thermal efficiency (~50%) compared to the fossil-fuelled plant (80-85%). Some modification in design and operation, such as: selecting the bayonet type of reformer equipped with orifice baffle, and enhancing heat utilization, can improve the lack of condition and are capable to increase the thermal efficiency of nuclear heated natural gas steam reformer to reach about 78%.Keywords: IHX, natural gas steam reforming, high temperature nuclear reactor ABSTRAKASPEK KESELAMATAN PADA APLIKASI REAKTOR NUKLIR SUHU TINGGI UNTUK PROSES STEAM REFORMING GAS ALAM. Telah dilakukan pengkajian aspek keselamatan pada aplikasi reaktor nuklir suhu tinggi untuk proses steam reforming gas alam. Aspek keselamatan dasar pada kopel reaktor nuklir dengan proses kimia adalah mencegah kemungkinan lepasnya bahan-bahan radioaktif ke lingkungan dan atau ke zona proses kimia. Pada kopel nuklir untuk proses kimia, digunakan penukar panas intermediate (IHX) sebagai interface yang memisahkan antara zona nuklir dengan zona proses kimia. IHX adalah penukar panas helium-helium, dimana helium primer (905oC) mampu memindahkan panasnya ke helium sekunder (890oC). Untuk menjaga agar tidak terjadi lepasan bahan-bahan radioaktif dari zona nuklir, diterapkan sistem keseimbangan tekanan, yaitu tekanan proses kimia (4,5 MPa) dirancang lebih besar dari tekanan helium sekunder (4,1 MPa) maupun helium primer (4,0 MPa). Rancangan ini mengakibatkan kondisi operasi panas proses yang mampu disediakan oleh reaktor nuklir menjadi tidak optimal yaitu hanya mencapai sekitar 800oC pada daerah tabung katalisator. Kondisi ini mengakibatkan efisiensi termal steam reforming gas alam dengan panas nuklir hanya mencapai 50%, jauh di bawah proses dengan sumber panas bahan bakar fosil (80-85%). Sejumlah modifikasi desain operasi, seperti memanfaatkan reformer tipe bayonet yang dilengkapi dengan orifice baffle, dan peningkatan efektivitas pemanfaatan panas, mampu meningkatkan efisiensi termal steam reforming gas alam dengan panas nuklir menjadi sekitar 78%.Kata kunci: IHX, steam reforming gas alam, reaktor nuklir suhu tinggi